Identification of factors that may influence the selection of first‐line biological therapy for people with psoriasis: a prospective, multicentre cohort study. (1st September 2017) - Davison, N.J.; Warren, R.B.; Mason, K.J.; McElhone, K.; Kirby, B.; Burden, A.D.; Smith, C.H.; Payne, K.; Griffiths, C.E.M.
Summary: Background: The Psoriasis Stratification to Optimise Relevant Therapy (PSORT) consortium has a collective aim to develop a prescribing algorithm to help stratify eligible patients with psoriasis to the most appropriate biological treatment. To facilitate the adoption of a stratified approach, it is necessary to first understand the factors driving the choice of first‐line biological therapy. Objectives: To identify and quantify factors that influence the selection of the first‐line biological therapy for people with psoriasis. Methods: Multinomial logistic regression was used to determine the factors that influenced the probability of treatment selection, using data from the British Association of Dermatologists Biologic Interventions Register from January 2012 to December 2015. Sensitivity analyses were performed to assess the robustness of the findings to key assumptions. Results: The main analysis was based on a dataset comprising 3040 people with psoriasis. The identified factors affecting first‐line biological selection within the available therapies were: presence of psoriatic arthritis; patient weight; employment status; country of registration; and baseline disease severity. Importantly, the analysis showed a general shift in prescribing behaviour over time. These results were robust to sensitivity analysis. Conclusions: This study offers important insights into the factors influencing current prescribing practice for first‐line biological therapies for people with psoriasis. It provides baseline data to inform the evaluation of future potential changes that may affect prescribing behaviour, such as stratified medicine.